O consumo de mídia por agricultores familiares e as mediações de classe social e economia solidária - Rebellato, Mauricio (2021)
This work is an ethnography study about media consumption by family agriculture of Santa Maria/RS, participants in the Project Esperança/Cooesperança and who are organized through the social movement of the Solidary Economy. This research is guided by the mediation of social class, understood as a key to understanding the relationships between the construction of class identity, the socio-cultural context and the consumption of the media. The main objective is to understand the role of media consumption, mediated by the solidary economy and by the social class, in the formation of the family agriculture class identity. We sought, during the two years of research, to answer the following research problem: How does media consumption, mediated by the social movement of the solidary economy, modulate the construction of the class identity of family agriculture’ families? For this, we base research on British and Latin American Cultural Studies, through the concept of social class (BOURDIEU, 1984) and the Theory of Mediations (MARTÍN-BARBERO, 2003) based on sociality and rituality. We used the method of critical ethnography reception (RONSINI, 2011), and other techniques based on a multimethodological combination (BONIN, 2014). The results of this research show that the mediations of sociality and rituality are also fundamental to the understanding of the results, with the social class and the solidary economy determining the practices and the way of life of family agriculture. Participation in the solidary economy movement, in turn, mould family life and affects the economic and cultural capital of farmers. The presence of media cultural capital (RONSINI, 2012) is revealed due to the increasing incorporation of means of communication for use in field work. Finally, we emphasize that the identity of family agriculture is built, on the one hand, in continuity and rupture with the peasant identity; on the other hand, as a means of cultural and social valorization, with a minimum counterpart of economic valorization.